O aprendizado da medicina baseada em evidências no curso de medicina da UFSCar - Primon, Aline (Universidade Federal de São Carlos, 2023)
Final paper presented to the Department of Medicine of the Federal Univeristy of São Carlos, aproaching the learning and usage of Evidence-Based Medicine troughout the course. It was accomplished trough a bibliographic review of PubMed and Scielo databases using the key-words "evidence-based medicine" and "active learning methodologies". Afterwards, a reflexive narrative about the learning of the scientific method and application of Evidence-Based Medicine was made.
The learning of evidence-based medicine at UFSCar's medical course
Keywords: Medicina; Metodologias ativas de ensino; Medicina baseada em evidências; Medicine; Active learning methodologies; Evidence-based medicine; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA